Spatial Diversity and the Dynamics of Entrepreneurial Ecosystems. The Perspective of Sustainable Development - Miszczak, Katarzyna; Mempel-Śnieżyk, Anna (European Journal of Sustainable Development, 2025)
the Entrepreneurial Ecosystem (EE) approach has gained prominence for conceiving an articulated system of various actors that influence the environment for the generation of high-impact ventures (Brown & Mason, 2017; Mack & Mayer, 2016). The EEs approach seeks to analyse, from the interaction between various actors, the development of enterprises at local, regional or national levels, taking the entrepreneur as the key actor in the process (Brown & Mason, 2017; Spigel & Harrison, 2018). EE are dynamic systems influenced by spatial diversity and socio-economic interactions. This article proposes a theoretical framework to analyse the multidimensional dynamics of entrepreneurial ecosystems in the context of sustainable development. Spatial diversity as a factor shaping the structure, efficiency, and adaptability of entrepreneurial ecosystems means that geographic, social, economic, cultural, and institutional diversity plays a key role in shaping the functioning of these ecosystems. The study considers the interdependence between spatial configurations and the systemic components of entrepreneurial ecosystems. By conceptualising interactions, the research advances theoretical insights into the spatial and dynamic nature of entrepreneurial ecosystems, addressing gaps in the existing literature and proposing a novel approach to understanding their complexity. Keywords: entrepreneurial ecosystem, sustainable development, local and regional development